유방암세포에서 괴화 에탄올 추출물의 NF-kB 의존적인 MMP-9 발현의 조절 규명을 위한 연구 - 김정미(Jeong Mi Kim); 이영래(Young Rae Lee); 황진기(Jin Ki Hwang); 김미성(Mi Seong Kim); 김하림(Ha Rim Kim); 박연주(Yeon Ju Park); 유용욱(Yong Ouk You); 김성철(Seong Cheol Kim); 류도곤(Do Gon Ryu); 권강범(Kang Beom Kwon) (동의생리병리학회지, 2014)
Flos Sophorae, the dried flower bud of Sophora japonica L, possesses anti-inflammatory properties, prevents and treats blood capillary and hypertension diseases and can also be used as a hemostat. However, the effect of Flos Sophorae on breast cancer invasion is unknown. Matrix metalloproteinase-9 (MMP-9), which degrades the extracellular matrix, is a major component in cancer cell invasion. In this study, we investigated the inhibitory effect of Flos Sophorae extract (FSE) on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced Matrix metalloproteinase-9 (MMP-9) expression and cell invasion, as well as the molecular mechanisms involved in Michigan Cancer Foundation-7 (MCF-7) cells. FSE inhibited the TPA-induced transcriptional activation of nuclear factor-kappa B (NF-κB). These results indicate that FSE-mediated inhibition of TPA-induced MMP-9 expression and cell invasion involves the suppression of NF-kB pathway in MCF-7 cells. Thus, FSE may have therapeutic potential for controlling breast cancer invasiveness. KCI Citation Count: 1